Energy consumption and economic growth:a panel analysis - Chye, Xiao Hui (Universiti Malaysia Sarawak, UNIMAS, 2009)
The main purpose of this study is to investigate the relationship between energy consumption and economic growth between 17 Asian countries, using annual time series and cross sectional data covering the period from 19 80 to 2006. Panel tests are applied in this study. The conclusions are: first, energy consumption and Gross Domestic Product (GDP) are stationary in the first difference. Second, results show a cointegration between these two variables, which indicate that GDP and economic consumption are moving together in a long run relationship. Third, energy consumption has a positive effect on GDP. Fourth,energy consumption does Granger cause to GDP in the short run and there exists a long run causal linkage running from GDP to energy consumption. This indicates that energy is a force for economic growth in the short period of time but development of economies is less dependent on energy in the long term. Some policies have been recommended in this study that could be carried out by the government of these Asian countries as to support the economic development for future.